2017
DOI: 10.4103/ija.ija_132_17
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia for electroconvulsive therapy: An overview with an update on its role in potentiating electroconvulsive therapy

Abstract: Despite advances in pharmacotherapy, electroconvulsive therapy (ECT) remains a mainstay treatment option in psychiatry since its introduction in 1930s. It can be used primarily in severe illnesses when there is an urgent need for treatment or secondarily after failure or intolerance to pharmacotherapy. The 'unmodified' technique of ECT was practised initially, with a high incidence of musculoskeletal complications. Several modifications including general anaesthesia and muscle relaxation are used to increase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 29 publications
1
34
0
7
Order By: Relevance
“…Thus, of all induction agents, etomidate is best suited to maintain cardiovascular stability especially in patients with coronary artery disease, cardiomyopathy, valvular heart disease, cerebral vascular disease, or hypovolemia. [ 21 ] Hemodynamic stability observed with etomidate may be due to its unique lack of effect on the sympathetic nervous system and baroreceptor functions. [ 22 ] In various studies, etomidate has shown less cardiovascular depression and it minimizes the use of vasopressor agents as compared to other induction agents in sepsis and critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, of all induction agents, etomidate is best suited to maintain cardiovascular stability especially in patients with coronary artery disease, cardiomyopathy, valvular heart disease, cerebral vascular disease, or hypovolemia. [ 21 ] Hemodynamic stability observed with etomidate may be due to its unique lack of effect on the sympathetic nervous system and baroreceptor functions. [ 22 ] In various studies, etomidate has shown less cardiovascular depression and it minimizes the use of vasopressor agents as compared to other induction agents in sepsis and critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…Önerilen ortalama doz 1,5-2,5 mg/kg'dır. Tiyopentalin, metoheksital ile karşılaştırıldığında daha sık bradikardi ve ventriküler aritmilere yol açtığı bildirilmektedir [19].…”
Section: Kısa Etkili Barbitüratlarunclassified
“…Anestezi enjeksiyonunun başlangıcı ile EKT uyarısının başlangıcı arasındaki zaman aralığı (ASTI) nöbet süresi ve kalite sonuçları üzerinde önemli bir etkiye sahip olabilir. ASTI, yaş gibi nöbet kalitesini kuvvetle etkilediği bilinen diğer faktörlerden daha büyük bir etkiye sahiptir [19].…”
Section: Anestezi Ve Ekt Uygulama Zaman Aralığıunclassified
See 2 more Smart Citations